Analysis of Factors Affecting User Satisfaction on SinegesJuara Application Using TAM and EUCS - Baldah, Azizah; Nugroho, Nicolaus Euclides Wahyu (Journal of INISTA, 2023)
SinegesJuara is an attendance application developed to provide real-time student attendance monitoring, allowing students to access and record their school attendance flexibly. Despite its popularity, SinegesJuara faces user challenges that have prompted researchers to investigate user satisfaction levels. This research analyzed user satisfaction factors by combining the TAM and EUCS methods, aiming to understand user satisfaction with the application. The research utilized the Slovin formula to determine a minimum sample size of 91 participants. Data analysis was conducted using the SEM-PLS approach with SmartPLS 3.2.9 software. The research findings indicate that the user satisfaction level with the SinegesJuara application is 78.77%, falling into the "Satisfied" category. This demonstrates that SinegesJuara fulfills its objectives, leading to user satisfaction. The results of the TAM method show that the Perceived Usefulness variable obtained a t-statistic value of 2.081, and the Attitude Toward Using variable obtained a t-statistic value of 7.877. Similarly, with the EUCS method, the Format variable obtained a t-statistic value of 2.445. As a result, it can be concluded that these three hypotheses significantly influence user satisfaction with the SinegesJuara application. In comparison, the other five hypotheses are rejected because they do not have a significant impact.